Representation of the Artistic and Political Life of Poland in the 20-30s of the XX century in Chervonyy Shlyakh Magazine - Loshchynska Nataliia (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is the analysis of Polonistics in the columns of the organ of the Ukrainian Soviet literary forces, the literary, artistic, and socio-political magazine Сhervonyy shlyakh (Red Way). Research methods. The research uses general scientific methods of cognition: inductive, analytical, comparative, generalization of information, historical-narrative. Due to their application, it became possible to more thoroughly investigate journal publications of various types about the specifics of the perception of contemporary Polish cultural and political life by citizens of Soviet Ukraine, as well as to establish the connection links between Polish and Ukrainian literature. The scientific novelty consists in the detailed processing of a large mass of information, namely magazine publications for the 13 years of existence of the monthly Сhervonyy shlyakh and the systematization of ones included in the concept of Polonistics. Conclusions. Сhervonyy shlyakh played a significant role in establishing international contacts, took an active part in establishing feedback between foreign and Ukrainian cultural figures. A significant place in it was occupied by Slavic studies in various manifestations. Due to the historical conditions that arose with the formation of the USSR, the main attention in the magazine Сhervonyy shlyakh was devoted to Russian and Belarusian studies. Poland, which was Ukraine’s closest neighbor outside the USSR, always attracted increased attention from both contributors and readers. Despite the political, ideological and even military conflicts between the states, ancient genetic ties prevailed and manifested mainly through numerous joint projects in the cultural and artistic life. It is these continuous contacts that the author of the article shows through the prism of Сhervonyy shlyakh - one of the popular magazines of Ukraine at that time.